Locked up, locked out : young men in the juvenile justice system - Nurse, Anne, 1968- (Nashville, Tenn. : Vanderbilt University Press, 2010)
"You disrespect somebody and he disrespects you. It's all about respect when you're locked up."
An introduction to the juvenile justice system -- Incarcerated youth and their worlds -- Institutional order -- Youth culture on the inside -- Contact with the outside -- Coming home -- Policy directions.
Includes bibliographical references (pages 181-196) and index.
Print version record.
Keywords: Juvenile justice, Administration of -- United States; Juvenile detention homes -- United States; Juvenile delinquents -- United States; Young men -- United States; SOCIAL SCIENCE -- Criminology; Juvenile delinquents; Juvenile detention homes; Juvenile justice, Administration of; Young men; United States; Electronic books